Small-scale fishing and Covid 19 the case of the local fishery supply chain in Bucaya, San Joaquin - Silfavan, Aldwin S
The local fishery supply is just as important as all other food supplies especially as shown during the COVID-19 pandemic. But having small-scale fishers who are already challenged even before COVOD-19, what further challenges can COVID-19 bring to them and the local fishery supply chain? This study aimed to describe the small-scale fishing in Bucaya, a coastal community in Southern Iloilo, and discuss the impacts of COVID-19 on the small-scale fishing and fishery supply chain in the area. A total of 27 respondents were purposively interviewed using a semi- structured interview guide and inquired about the impacts of COVID-19 on small-scale fishing and the local fishery supply chain. Secondary data were drawn from articles published in reputable journals, news articles, polciy briefs, and situationer reports from government department, agencies, and bureaus. Results show that fishing in Bucaya is longstanding and accompanied by various developments in gear, fishing equipment or materials, and other developmental aspects of fishing and the fisher. Meanwhile, COVID-19 had varied impacts on inshore and offshore small-scale fishing in the barangay. The players on the local fishery supply chain were exposed to COVID-19, including mental-emotional distress and economic challenges, movement restrictions, and travel restrictions which created severe impacts that limited fishing operations or capacity, decreased fish demand, strained the marketing of fish, revealed gender differences, and diminished household income. However, with the role later assumed by the LGU and the online platforms the condition improved.